Utilization of elderly donors in liver transplantation for patients with hepatocellular carcinoma: A national retrospective cohort study of China. (September 2022) - Hu, Liangshuo; Zhao, Zhen; Mu, Fan; Dong, Siyi; Zhang, Chun; Shi, Jianhua; Tian, Min; Guo, Kun; Zhang, Xufeng; Yu, Liang; Lv, Yi; Wang, Bo
Abstract: Background: Profound organ shortages worldwide have led to the increased utilization of marginal organs from older individuals. However, the effectiveness of liver transplantation (LT) with organs from elderly donors for patients with hepatocellular carcinoma (HCC) remains controversial. The objective of the current study was to assess the overall survival (OS) and disease-free survival (DFS) of patients with HCC following LT using grafts from deceased donors over 60 years old. Material and methods: Patients with HCC who underwent LT between 2015 and 2018 were identified in the China Liver Transplant Registry database. The overall survival and disease-free survival of older liver donors (OLDs) were compared with those of younger liver donors (YLDs) after propensity score matching. Results: From January 2015 to December 2018, a total of 4971 HCC patients were enrolled in the study according to the screening criteria. The absolute and relative utilization of liver grafts from elderly patients over 60 years for HCC patients increased every year, from 65 (9.3%) in 2015 to 268 (14.5%) in 2018. Disease-free survival (DFS) was significantly lower in HCC patients with elderly donors (both P < 0.05) after propensity score matching. The OLD group had worse DFS than YLD group if patients had tumors beyond the Milan criteria (P < 0.05). Conclusions: The use of older donors for LT has been growing quickly in the last few years in China. Grafts from older donors can be safely used in HCC recipients with similar OS and comparable perioperative complications. However, further investigation into whether older donor has an impact on recurrence is warranted, especially among those with tumors beyond the Milan criteria. Highlights: The use of older donors had been growing quickly in the last few years in China. Older donors can be safely used in hepatocellular carcinoma recipients. Early recurrence should be alert for patients beyond Milan criteria with old donors.